2017
DOI: 10.1371/journal.pone.0180062
|View full text |Cite
|
Sign up to set email alerts
|

Playing with fire – What is influencing horse owners’ decisions to not vaccinate their horses against deadly Hendra virus infection?

Abstract: Hendra virus is a zoonotic paramyxovirus, which causes severe respiratory and neurological disease in horses and humans. Since 2012, the Hendra virus sub-unit G vaccine has been available for horse vaccination in Australia. Uptake of the vaccine has been limited and spill-over events of Hendra virus infection in horses continue to occur. We conducted an online, questionnaire-based cross-sectional study of 376 horse owners belonging to a variety of different equestrian clubs in Queensland, Australia, to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
(45 reference statements)
1
27
0
1
Order By: Relevance
“…18,19 The initial requirement for boosters to be administered at 6-monthly intervals, and the delay in APVMA approval for use in pregnant mares until 2016, were also likely reasons for some to conclude that there may have been early safety and efficacy concerns with the vaccine and that veterinarians' recommendations to vaccinate were largely motivated by financial gain. 18,19,31 All facets of the safety, efficacy and adverse reaction reporting process were reviewed by the Queensland Parliamentary Inquiry in 2016, with the vaccine being verified to be safe and effective. 20,32 Because of the very significant human health, horse health and welfare, biosecurity and workplace health and safety implications of HeV disease, the Australian Veterinary Association recommends that the vaccine should only be available to, and transported, stored and administered by registered veterinarians in order to fulfil the current label conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The initial requirement for boosters to be administered at 6-monthly intervals, and the delay in APVMA approval for use in pregnant mares until 2016, were also likely reasons for some to conclude that there may have been early safety and efficacy concerns with the vaccine and that veterinarians' recommendations to vaccinate were largely motivated by financial gain. 18,19,31 All facets of the safety, efficacy and adverse reaction reporting process were reviewed by the Queensland Parliamentary Inquiry in 2016, with the vaccine being verified to be safe and effective. 20,32 Because of the very significant human health, horse health and welfare, biosecurity and workplace health and safety implications of HeV disease, the Australian Veterinary Association recommends that the vaccine should only be available to, and transported, stored and administered by registered veterinarians in order to fulfil the current label conditions.…”
Section: Discussionmentioning
confidence: 99%
“…19 The regulatory requirement for veterinary-only administration of the vaccine resulted in mistrust of private veterinarians, who were perceived by some in the horse industry to be motivated only by a vested financial interest. 19,31 Studies have also shown evidence of significant levels of distrust towards the vaccine manufacturer by some horse owners in regard to adverse vaccine reactions not being followed up or reported appropriately to the APVMA. Comments made by some horse owners suggest that veterinarians and the vaccine manufacturer were perceived to be in collusion.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the use of an animal vaccine, for example, a quantitative study could determine the proportion and demographic characteristics of owners who give the vaccine to their animals over a set period of time. Similarly, questionnaires that try and capture people's intentions can test the relative importance of different factors thought to be important to their decisions through the statistical analysis of responses to a series of standardized closed questions [See (8,9) for example]. However, unless participants have the opportunity to respond to open questions in their own words then the research cannot capture novel and unanticipated information.…”
Section: Foundations and Shared Assumptions In Qualitative Research Mmentioning
confidence: 99%
“…comm.). 1,12 Although a range of vaccine types are available internationally, there is only one commercially available in Australia (Equivac®S/Equivac 2 in 1®; Zoetis, NSW, Aust). This vaccine is derived from an acid-extracted preparation of S. equi, administered IM.…”
Section: Abstract Bacteriology; Equine Diseases; Horses; Immunology; mentioning
confidence: 99%